Background‐free wide‐field fluorescence imaging using edge detection combined with HiLo. Issue 8 (13th May 2022) - Hu, Yuyao; Liang, Dong; Wang, Jing; Xuan, Yaping; Zhao, Fu; Liu, Jun; Li, Ruxin
Abstract: Fluorescence microscopy has been widely used in the field of biological imaging, but the disturbance of background noise has always been an unavoidable phenomenon. To obtain a background free image, a virtual HiLo based on edge detection (V‐HiLo‐ED) method for background removing is proposed, which is different from the existing popular software algorithms that obtain the background‐free image by subtracting the estimated background, but the background‐free image is directly reconstructed by estimating the foreground. Compared with two other popular software‐based methods, the wavelet‐based background and noise subtraction algorithm (WBNS) and the rolling ball algorithm (RBA), the V‐HiLo‐ED owns a better quality on achieving background‐free imaging. Compared with hardware‐based method such as HiLo method, V‐HiLo‐ED exhibits almost the same performance but faster speed. In combination with light sheet microscopy, the V‐HiLo‐ED further improves the signal‐to‐noise ratio of images with thick light‐sheet. These experiment results indicate that the V‐HiLo‐ED owns the potentiality in many other image applications such as endoscopy. Abstract : To remove the background noise in fluorescence imaging, a virtual HiLo based on edge detection (V‐HiLo‐ED) method is proposed, which reconstructs background‐free images directly by estimating the foreground. Compared with popular software‐based methods and hardware‐based methods, V‐HiLo‐ED shows unique advantages in the balance of the output figure quality and image speed, respectively, which indicate that the V‐HiLo‐ED owns the potentiality in many image applications.